Algerian Socialism and the Architecture of Autogestion. Issue 1 (15th October 2019) - Crane, Sheila
Abstract : In a series of essays published in 1966 as L'arceau qui chante [ The Arch That Sings ], the architect Abderrahman Bouchama outlined a new path for a post-revolutionary Algerian architecture. Bouchama's text responded to ambitious efforts to construct a revolutionary socialist state immediately following Algeria's independence in 1962. Significantly, President Ahmed Ben Bella's policies of autogestion, or self-management, aimed to fuel the reallocation of property, the redistribution of resources, the restructuring of labor, and the redefinition of national culture, efforts that encouraged a radical rethinking of architecture and the construction industry. While Bouchama was certainly the most prolific architectural theorist at the time, his writings and built projects might be productively set in dialogue with contemporaneous efforts by Anatole Kopp, Pierre Chazanoff, and Georgette Cottin-Euziol to articulate what I argue was a provocative architecture of autogestion . Algeria's brief experiment with autogestion imagined a path towards socialism rooted in the new nation's revolutionary origins, even as it repositioned the Maghrib as a defining center for Afro-Asian and pan-Islamic solidarity, an impulse that was articulated powerfully in Bouchama's writings. Attending to this episode suggests the critical importance of provincializing Marxist architectural theory and practice, a project that requires paying closer attention to important strands of anti-imperialist struggle within Marxist theory and praxis that operated outside of its familiar centers.